Moving out of agriculture: Structural change in Viet Nam - McCaig, Brian; Pavcnik, Nina (International Food Policy Research Institute, 2017)
During the past 20 years, Viet Nam underwent an economic transformation, featuring high rates of economic growth—real GDP increased at an average annual growth rate of 7 percent from 1986 to 2008 and GDP per capita in PPP terms tripled—and a sharp drop in poverty rates. These changes catapulted Viet Nam out of the poorest quintile of countries (ahead of Cambodia and Bangladesh, but behind Laos and Kenya) in 1986, when its GDP per capita in PPP (2005 international dollars) was around only $800. At that point, the highly agrarian nature of Viet Nam’s economy placed it in the top quintile of countries with the largest share of agriculture in GDP and among the top 10 percent of countries with the highest share of workers in agriculture throughout the 1990s.